1993
DOI: 10.1159/000227196
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Alkaline Phosphatase and Carcinoembryonic Antigen in Lung Cancer Patients

Abstract: Leukocyte alkaline phosphatase (LAP) scores in peripheral blood and plasma carcinoembryonic antigen (CEA) levels were determined in 58 lung cancer patients and compared with those of 22 healthy persons, who served as controls. In the control group we found LAP scores of 54 + 28 and CEA levels of 4 + 3 ng/ml. The 97.7% confidence intervals are: LAP score < 110 and CEA level 10. In the patients with limted lung cancer we found LAP scores of 152.4 + 36.7 and CEA levels of 22.7 + 48 ng/ml. The 97.7% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…In all cases that have been studied in Assaf Harofeh [1][2][3][4][5] as well as in the present work it was found out that whenever métastasés were diagnosed in a patient, the LAP score was much higher than its regular value for that patient. Thus the present study shows that the LAP test yields an earlier detection of métastasés in many cases.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In all cases that have been studied in Assaf Harofeh [1][2][3][4][5] as well as in the present work it was found out that whenever métastasés were diagnosed in a patient, the LAP score was much higher than its regular value for that patient. Thus the present study shows that the LAP test yields an earlier detection of métastasés in many cases.…”
Section: Discussionsupporting
confidence: 56%
“…In a previous paper we showed that the average LAP score in metastatic patients is significantly higher than in nonmetastatic patients, but the overlap between 95% confidence level ranges of the scores of metastatic patients and nonmetastatic patients is such that there is no reliable threshold value that could distinguish between the stages [5], In this study we consider the LAP scores of nonmetastatic patients that were tested for LAP score as a part of their periodical checkups and who later became metastat ic. The purpose of this study is to observe, in the same patient, the time behavior of his LAP scores, and to find out if there was a rise in the LAP score that started before métastasés have been diagnosed by the usual methods, and thus could have served as a predictor and warning signal to the physician.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of ALP activity is frequently used in clinical medicine. The cancer-related research of the enzyme is focused on the eutopic or ectopic expression of ALP in several malignancies including brain tumors (Takahara et al, 1982;Curatolo et al, 1992;Bacci et al, 1993;Hoshino et al, 1993;Moro et al, 1993;Stieber et al, 1993;Walach and Gur, 1993). An understanding of the reasons underlying increased expression of ALPs may provide insights into the process of carcinogenesis and normal functions of the enzyme.…”
mentioning
confidence: 99%
“…The determination of LAP may also be used for other purposes, such as to evaluate neutrophilic function (5), discriminate chronic neutrophilic leukemia (6), and as complementary laboratory criteria to discriminate between polycythemia vera and secondary polycythemia (7). In addition, the LAP assay has been proposed as a means of distinguishing between malignant and benign paraproteinemias (8), as a predictor of the metastatic state of breast and colorectal cancer (9), and as a prognostic test for lung cancer (10). It is possible that further applications for LAP determination will be discovered in the future.…”
Section: Introductionmentioning
confidence: 99%